PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU DI SEKOLAH DASAR NEGERI 5 SINTANG - Simson, Simson; Chiar, Chiar; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The principal is a leader in a school institution that has a very important role as managers, leaders, motivators in educational institutions, and responsible in fostering subordinates of teachers, administrative staff to achieve the goal of hope in improving the quality of school. The focus of the problem in this research is: